O estudo da radiação X: desenvolvendo uma estratégia de ensino para a aprendizagem significativa - Jesus, Jarbas da Silva de (2015)
This work had as it main goal the development of an educational product (Didactic Sequence) which is capable of enabling a meaningful learning of Modern and Contemporary Physics concepts from the X Radiation production and Emission Theory During High School years. The current work discussed the influence of the use of a didactic sequence, made upon the Méheut model and based on the Ausubel meaningful learning theory, in the insertion of Modern and Contemporary Physics in High School, through the use of the X radiation production and emission theory as the main theme. A quantitative analysis was performed by using the Pearson's Chi-squared test to verify the likely association between the didactic sequence use and the students' educational achievement from questionnaires elaborated according to the revised Bloom taxonomy.A conceptual maps analysis was performed based on the progressive differentiation and the integrating reconciliation of concepts to verify the occurrence of a meaningful learning by the students related to the X radiation theory conceptions. The quantitative analysis outputs demonstrated a statistically significant association between the experimental classroom students' performance and the use of the educational product (Didactic Sequence), whilst the conceptual maps analysis indicated the occurrence of a meaningful learning based on the progressive differentiation and the integrating reconciliation of concepts, which validates such educational strategy developed for the teaching of Modern and Contemporary Physics during High School Years.